The impact of COVID-19 on poverty in South Africa - Pillay, Nuvika (School of Economics, 2024)
This paper analyses how the COVID-19 pandemic has impacted money-metric poverty in South Africa. Against a backdrop of already rising poverty-levels, the pandemic is expected to have a devastating impact on the most vulnerable population groups. Using the recently released 2020 and 2021 General Households Surveys, this thesis presents the first nationally representative estimates of poverty during the heart of the pandemic and as the country began economically recovering. The comparability of the General Household Surveys conducted telephonically during the pandemic is interrogated. The paper finds that an estimated 2.8 million people entered upper-bound poverty and an additional 1.5 million people were food poor in 2020. The increase in poverty would have been substantially worse without the additional COVID-19 grant top-ups. The 2021 poverty estimates report a dramatic poverty recovery by October 2021, with estimated poverty levels lower than they were in 2019. Even vulnerable groups, like female-headed or black-headed households, experience this fall in extreme poverty. The surprising result is explained by the continuation of the Social Relief of Distress grant into 2021 which provides the ‘working poor', and large number of South Africans unemployed prior to the pandemic, grant support they were previously excluded from